Chemical composition and species identification of microalgal biomass grown at pilot-scale with municipal wastewater and CO2 from flue gases - Lage, Sandra; Gentili, Francesco (2023)
The production potential of a locally isolated Chlorella vulgaris strain and a local green-algae consortium, used in municipal wastewater treatment combined with CO2 sequestration from flue gases, was evaluated for the first time by comparing the elemental and biochemical composition and heating value of the biomass produced. The microalgae were grown in outdoor pilot-scale ponds under subarctic summer conditions. The impact of culti-vation in a greenhouse climate was also tested for the green-algae consortium; additionally, the variation in species composition over time in the three ponds was investigated. Our results showed that the biomass produced in the consortium/outdoor pond had the greatest potential for bioenergy production because both its carbohy-drates and lipids contents were significantly higher than the biomasses from the consortium/greenhouse and C. vulgaris/outdoor ponds. Although greenhouse conditions significantly increased the consortium biomass's monounsaturated fatty acid content, which is ideal for biodiesel production, an undesirable increase in ash and chemical elements, as well as a reduction in heating value, were also observed. Thus, the placement of the pond inside a greenhouse did not improve the production potential of the green-algae consortium biomass in the current study infrastructure and climate conditions.